The Relevance of Air Transport in Nigeria and Its Social-Economic Significant on National Development - Amos Ojo Adedeji, Ph.D (International Journal of Business and Quality Research, 2024)
Development is crucial and essential to the sustenance and growth of any nation, while greatest achievement of any government is reaching a higher level of development, which makes its people naturally attached to it. Air transportation system is vital for economic vitality of any country, and has been categorized as one of the most important engine for economic development. The study interrogates Nigeria’s social-economic development through air transport. The study chose economic theory of infrastructure as its theoretical framework. Qualitative analysis was also chosen to carry out the task of the work. Tax contribution, foreign direct investment attraction, employment opportunities, boosting productivity across national economy, improvement of quality of life, provision of vital connectivity among different regions within Nigeria, and promotion of social inclusion and belongingness were identified as social-economic impact of air transport in Nigeria. The paper found poor funding, overstretched and decaying facilities, corruption and bad management, and poor security among other factors militating the effectiveness of air transport in Nigeria. The study concluded by recommending among others adequate funding, provision of modern infrastructural facilities, and putting in place mechanism to curb corruption in the sector. Investing in modern security measures and devices is also key.